LIVrE - Neo, Wen Ling (2016)
LIVrE is an interactive art installation that explores the themes of reading and its relation to imagination. The name comes from a combination of the word ‘Live’ and ‘Livre’, the French word for book. This translates into (Live) Book which is what our artwork is. We propose to infuse modern technology into physical books, to allow people to experience reading in an unconventional way and encourage readers to continue to stimulate their imagination through reading.